Effect of temperature on relative permeability – Role of viscosity ratio. (15th October 2020) - Esmaeili, Sajjad; Modaresghazani, Jafar; Sarma, Hemanta; Harding, Thomas; Maini, Brij
Abstract: Although there are many studies regarding the effect of temperature on relative permeability, there is no consensus on this issue. Here we examine the role of oil/water viscosity ratio in making the measured oil/water relative permeability dependent on temperature. Two-phase oil/water relative permeability was carefully measured over a wide range of temperature between 23 °C and 210 °C using a poly-alpha-olefin (PAO) oil and deionized water in a clean unconsolidated sand-pack at confining pressure of 800 psi. A sophisticated experimental setup that is capable of measuring the pressure drop and monitoring the temperature in four different length segments of the sand-pack was used. Both the Johnson, Bossler and Neumann (JBN) method and the history match approach were employed to obtain the relative permeability from the results of isothermal oil displacement tests. Furthermore, high-temperature and high-pressure interfacial tension (IFT) and contact angle measurements were also carried out. The results show that the two-phase oil/water relative permeability, in this ultra-clean system, is practically insensitive to the temperature, even though the oil/water viscosity ratio changes by two orders of magnitude. The slight variation in oil endpoint relative permeability and irreducible water saturation, especially at ambient condition, was attributed to the uncertainty in the oil viscosity measurement and reproducibility of the sand packing procedure. The IFT of this system declined from 41.1 mN/m at 23.5 °C to 20.9 mN/m at 185.2 °C and contact angle decreased from 80.7° at 23.5 °C to 56.9° at 150 °C. Changes of this level do not significantly affect the oil displacement behavior.